Design, construction, and optimization of a novel, modular, and scalable incubation chamber for continuous viral inactivation. (17th March 2017) - Orozco, Raquel; Godfrey, Scott; Coffman, Jon; Amarikwa, Linus; Parker, Stephanie; Hernandez, Lindsay; Wachuku, Chinenye; Mai, Ben; Song, Brian; Hoskatti, Shashidhar; Asong, Jinkeng; Shamlou, Parviz; et al.
Abstract : We designed, built or 3D printed, and screened tubular reactors that minimize axial dispersion to serve as incubation chambers for continuous virus inactivation of biological products. Empirical residence time distribution data were used to derive each tubular design's volume equivalent to a theoretical plate (VETP) values at a various process flow rates. One design, the Jig in a Box (JIB), yielded the lowest VETP, indicating optimal radial mixing and minimal axial dispersion. A minimum residence time (MRT) approach was employed, where the MRT is the minimum time the product spends in the tubular reactor. This incubation time is typically 60 minutes in a batch process. We provide recommendations for combinations of flow rates and device dimensions for operation of the JIB connected in series that will meet a 60‐min MRT. The results show that under a wide range of flow rates and corresponding volumes, it takes 75 ± 3 min for 99% of the product to exit the reactor while meeting the 60‐min MRT criterion and fulfilling the constraint of keeping a differential pressure drop under 5 psi. Under these conditions, the VETP increases slightly from 3 to 5 mL though the number of theoretical plates stays constant at about 1326 ± 88. We also demonstrated that the final design volume was only 6% ± 1% larger than the ideal plug flow volume. Using such a device would enable continuous viral inactivation in a truly continuous process or in the effluent of a batch chromatography column. Viral inactivation studies would be required to validate such a design. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:954–965, 2017